Integrasi Regresi dan Anova dalam Mengevaluasi Faktor Penentu Produksi dan Kontribusi Ekonomi Komoditas Perkebunan Tapanuli Selatan - Novita Aswan; Yusra Fadhillah; Rafik Anhar Tambunan; Riky Rivaldo Tambunan (JOSETA Journal of Socio-economics on Tropical Agriculture, 2025)
This article employs an integrated statistical approach to analyze production determinants and the comparative economic contributions of leading plantation commodities in South Tapanuli Regency (2014-2023). Multiple linear regression indicates that coffee (p=0.033) and cocoa prices (p=0.027) exert a significant positive influence on production, whereas land area demonstrates no significant effect. ANOVA results (F=11.048; p=0.000) reveal statistically significant disparities in contributions to the Regional Gross Domestic Product. Palm oil provides the highest mean contribution (4.66%), which differs significantly from rubber, coffee, and cocoa. No significant difference exists among the latter three commodities. Consequently, this integrated analysis furnishes a robust foundation for policy formulation: implementing price incentives is more efficacious than land expansion for coffee and cocoa development; palm oil necessitates sustainability-focused strategies; and rubber, coffee, and cocoa require product diversification to augment their value-added potential.